An analysis of a large multi-institutional database reveals important associations between treatment parameters and clinical outcomes for stereotactic body radiotherapy (SBRT) of oligometastatic colorectal cancer. (February 2022) - Sheikh, Saad; Chen, Hanbo; Sahgal, Arjun; Poon, Ian; Erler, Darby; Badellino, Serena; Dagan, Roi; Foote, Matthew C.; Louie, Alexander V.; Redmond, Kristin J.; Ricardi, Umberto; Biswas, Tithi
Highlights: The 1- and 5-year local recurrence rates were 13.6% and 44.3, respectively. The 2-and 5-year overall survival rates were 76.1% and 35.9%, respectively. A biological equivalent dose of ≥120 Gy led to an improvement in local recurrence. The presence of lung metastases was associated with improved local recurrence. A larger total PTV size (≥17.5 cc) was associated with worse OS, PFS, and WSP. Abstract: Purpose: In recent years, stereotactic body radiotherapy (SBRT) has emerged as an effective treatment for oligometastatic cancers. Here, we report radiation treatment parameters and clinical outcomes for patients with oligometastatic colorectal cancer (CRC) treated with SBRT using a large multi-institutional database. Methods: Patients with extra-cranial oligometastatic CRC (≤5 lesions) treated with SBRT at six large academic cancer centers were included. The primary outcome was local recurrence while secondary outcomes included overall survival (OS) progression free survival, oligo-progression, and widespread progression. Survival outcomes were estimated using the Kaplan-Meier method. Univariable and multivariable analyses were performed to determine the relationship between patient and treatment characteristics and clinical outcomes. Results: We identified 235 patients with a total of 381 oligometastatic CRC lesions. The 1- and 5-year local recurrence rate was 13.6% and 44.3% respectively. The median OS was 49 months with a 2-and 5-year OS of 76.1% and 35.9%, respectively. On multivariable analysis, a BED10 of ≥120 Gy, and lung versus liver metastases were associated with a reduction in local recurrence. Larger total PTV size (≥17.5 cc) was associated with worse overall survival, progression free survival, and widespread progression. Conclusion: This large multi-institutional analysis found that the use of SBRT for oligometastatic colorectal cancer resulted in favorable overall survival. However, local recurrence is higher than expected for ablative radiation treatment. An increase in BED10 should be considered if feasible and safe.